The impact of concentrated solar power in electric power systems: A Chilean case study. (1st February 2019) - Mena, R.; Escobar, R.; Lorca, Á.; Negrete-Pincetic, M.; Olivares, D.
Highlights: Capacity expansion planning model for the integration of CSP-TES. Evaluation of the systemic economic and operational benefits provided by CSP-TES. Analysis of multiple technology and policy scenarios for the Chilean power system. Study of complementarities between CSP-TES and other technologies. Investigation on the role of CSP-TES as a flexibility provider to the system. Abstract: This paper presents a study about the impacts of the integration of concentrated solar power (CSP) with thermal energy storage (TES) in electric power systems. The main tool for this study is a comprehensive long-term power system capacity expansion planning model that integrates a specific module to represent the operation of CSP-TES power plants. The model determines the optimal investments on generation and transmission assets over a twenty-year planning horizon, ranging from 2018 until 2037, and employs projections for the various parameters involved (e.g. load growth, capital costs for the different generation technologies, fuels costs). One of the main features of the model is its ability to capture the hourly operational dynamics of the system through the consideration of multiple representative days for each of its investment periods. This feature allows a better understanding of the role of CSP-TES as a significant provider of flexibility to support a high penetration of variable renewable energy sources, as compared with traditional planning models based on load blocks. The model is applied to a case study for the Chilean electricity system. In order to study the impacts of CSP-TES, various scenarios of future capital costs and carbon tax levels are defined and analyzed for two market dominant CSP-TES technologies. The results show that for low CSP-TES capital costs, or high carbon taxes, the integration of CSP-TES in the system is significant towards year 2037, potentially reaching about one third of the total dispatched energy in the Chilean electric power system, yielding important operational, economic, and environmental benefits.